2011
DOI: 10.2174/157016211795945269
|View full text |Cite
|
Sign up to set email alerts
|

Liver-Related Factors Associated with Low Vitamin D Levels in HIV and HIV/HCV Coinfected Patients and Comparison to General Population

Abstract: In our experience, despite the high prevalence of 25(OH)D insufficiency, HIV and HCV-infection did not seem to influence vitamin D status. The role of HIV, HCV and cART on hypovitaminosis D needs further validation in larger cohorts that account for the vitamin levels in general populations and for seasonal and regional variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 0 publications
2
34
1
Order By: Relevance
“…In addition, the median vitamin D level was >30 ng/mL in HIV/HCV co-infected patients. Our results reflect those reported in an Italian study, which found that median vitamin D serum levels >25 ng/ ml were similar in the HIV mono-infected, HIV/HCV co-infected and healthy controls [29]. Moreover, in a recent, large study on a general healthy population in Central Europe, Pludowski et al [30] reported an average vitamin D concentration of >30 ng/ml.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the median vitamin D level was >30 ng/mL in HIV/HCV co-infected patients. Our results reflect those reported in an Italian study, which found that median vitamin D serum levels >25 ng/ ml were similar in the HIV mono-infected, HIV/HCV co-infected and healthy controls [29]. Moreover, in a recent, large study on a general healthy population in Central Europe, Pludowski et al [30] reported an average vitamin D concentration of >30 ng/ml.…”
Section: Discussionsupporting
confidence: 90%
“…9 Results from these reports were quite inconsistent (Figures 2 and 3). The three matched case-control analyses 27 a significantly higher prevalence in healthy controls in another, 30 and a significantly higher prevalence in HIV-infected patients in the third. 34 The study with the higher prevalence in the control group was performed in African-American subjects, 30 who are usually regarded as being at high risk of hypovitaminosis D. 61 As a result, both cases and controls had a very high rate of hypovitaminosis D. Paul et al 34 found a 20% greater prevalence of 25OHD ,20 ng/mL in HIV-infected patients, but they enrolled a very small sample (70 cases and 35 controls).…”
Section: Vitamin D Deficiencymentioning
confidence: 94%
“…Nine studies compared vitamin D status between HIV+ and "healthy" subjects, 9,23,25,27,30,31,34,42,60 but only three of them were matched case-control analyses. 27,30,34 Overall, the studies were heterogeneous in terms of demographic and clinical characteristics of populations included. Even the data collected and the methods used to report the information were quite variable (eg, age and duration of ART therapy were described as mean ± standard deviation, median with interquartile range, or range).…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations